Medical Faculty Students' Attitudes, Behaviors and Beliefs About Covid-19 Pandemic - Osman Hasan Tahsin Kılıç; Murat Anıl; Merziye Gökçe Göksu; Umut Varol; Güven Güvendi; Bahadır Haytabey; Istemihan Coban; Berna Dirim Mete (Galenos Publishing House, 2021)
Objective: The aim of this study is to evaluate the attitudes, behaviors, and beliefs of medical faculty students about the covid-19 pandemic. Methods: Between 29/03/2020 and 04/13/2020 a total of 1,332 students had been questioned in three Turkish speaking countries (Turkey, Azerbaijan, Turkish Republic of Northern Cyprus). Results: The average age of the students were 20.1 +- 1.6. Among all 895 (67.7%) of them were female and 427 (32.3%) were male. 1020 (77.2%) of the studens were in Turkey, 195 (14.8%) were in Azerbaijan and 107 (8.1%) were in the TRNC. 104 of the students (7.9%) had a chronic disease. It was found that number of alcohol and cigarette users decreased significantly during the pandemic. (p <0.001, p <0.001). Anxiety levels of those who quit or reduced smoking were found to be higher than those who increased or did not change their amount of smoking (p=0.034). It was found that the most benefited sources were 'their faculty lecturers' (n=453, 34.3%), 'Worldometer ® website' (n= 449, 34%) and 'Youtube videos' (n=396, 30%). Conclusion: Longitudinal studies are needed on the effects of pandemic on alcohol and tobacco use. It is important to educate future physicians in social media literacy, interpretation and responsibilities for social media posts. In this way, perhaps we can contribute to minimize the public's erroneous beliefs and maladaptive behaviors regarding the pandemic and reduce stigmatizing attitudes towards physicians, elders and Asians